Development the some of bases of the trail knowledgeas basic partial scientists of the criminalistics - Ланцедова, Юлія Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
In article proposals the definition of the concepts of the trail knowledge and it place in technique, tactics and technique of the base training course of the criminalistics. Solved the essence and the species division of the antidelictual traces. Proposals the detail classification of the traces on trail forming objects.